2019
DOI: 10.1055/s-0038-1676971
|View full text |Cite
|
Sign up to set email alerts
|

Technology Access, Technical Assistance, and Disparities in Inpatient Portal Use

Abstract: Background Disadvantaged populations, including minorities and the elderly, use patient portals less often than relatively more advantaged populations. Limited access to and experience with technology contribute to these disparities. Free access to devices, the Internet, and technical assistance may eliminate disparities in portal use. Objective To examine predictors of frequent versus infrequent portal use among hospitalized patients who received free access to an iPad, the Internet, and technical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 50 publications
(74 reference statements)
1
19
1
Order By: Relevance
“… 9 , 10 , 15 In addition, studies of patient portals have found that within vulnerable patient populations, lack of familiarity and limited experience with technology present barriers to portal use. 16 …”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 , 15 In addition, studies of patient portals have found that within vulnerable patient populations, lack of familiarity and limited experience with technology present barriers to portal use. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Finally, training has been identified as critical to support portal use by both care team members and patients (Grossman et al., 2019; Hefner et al., 2018; McAlearney, Gaughan, et al., 2019), and these analyses suggested important training opportunities around both feature use and how to incorporate the tool into existing care team workflow. Improving patient training may help alleviate some of the training burden that care team members currently experience, especially if such training includes instructions about the use of features such as secure messaging and how to access more detailed technical assistance for those patients who need it.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to age, a digital divide has been found to exist by other demographic factors (Anderson & Perrin, 2017;Choi & DiNitto, 2013;DiMaggio et al, 2004;Grossman et al, 2019;Smith, 2014a;Werner et al, 2011;Yoon et al, 2020;Zickuhr & Smith, 2012). Older adults in the United States who have an average household income of at least $75,000 or more and those who are college graduates are more likely to use the internet than their poorer and less educated peers (Anderson & Perrin, 2017;Smith, 2014a, b).…”
Section: Digital Dividementioning
confidence: 99%